A Case of Acute Necrotizing Encephalopathy Associated with SARS-CoV-2 on the Background of Takayasu's Arteritis and Intensive Care Management - Emel Uyar; Gamze Gürsoy; Banu Çelikel Acar; Rana Beyoğlu; Aslınur Özkaya Parlakay; Serhan Özcan; Oktay Perk; Esra Koçkuzu; Serhat Emeksiz (Galenos Yayinevi, 2024)
Severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) typically leads to mild infectious disease in children, although both acute infection and multisystem inflammatory syndrome in children can cause severe complications. Additionally, SARS-CoV-2 is a neurotropic virus that can present with a wide spectrum of neurological symptoms. Acute necrotizing encephalopathy of childhood (ANE) is a rare acute encephalitis characterized by symmetrical lesions in the thalamus with variable involvement of the white matter, brainstem, and cerebellum. It usually develops after viral infection in genetically predisposed patients. Although the prognosis is poor, some patients respond to steroid and intravenous immunoglobulin (IVIG) treatment. In this case report, we present the case of an 11-year-old patient with no previously known disease who developed SARS-CoV-2-related ANE that did not respond to steroid and IVIG treatment. Our patient was incidentally diagnosed with Takayasu arteritis, and brain death occurred in the 32nd hour of admission.